IAN BUTTERWORTH CBE: 3 December 1930—29 November 2013 - Dornan, Peter (Biographical memoirs of fellows of the Royal Society, 2018)
Ian Butterworth was a major force in European particle physics from the start of the subject in the late fifties until leaving his post as the European Organization for Nuclear Research (CERN) research director in 1986 to become principal of Queen Mary College. Following his PhD at Manchester, he moved to Imperial College, where later he was head of both the high energy group and the physics department. His early research was dominated by bubble chamber analyses searching for resonant hadronic states, crucial for the establishment of the quark model. Investigating these resonances, using mass spectra and partial wave analyses, was his speciality. He had vision. He was one of the first to recognize the value of IT advances, the importance of networking and the vast potential of the Web. In 1990, at the age of 60, he had a stroke but less than a year later he was again active. His main interests became the effective use of the Web for electronic publishing and the advancement of a coherent European network strategy for education and research. Much of this was under the auspices of the Academia Europaea, of which he was vice president from 1997 to 2003. In his later years he retained a deep interest in European culture and gastronomy and continued to enjoy travelling around Europe. Ian was a special person, warm-hearted, lively and excellent company.